ANALISA PERUBAHAN KINERJA DI JALAN GAJAH MADA MEDAN AKIBAT ADANYA JALAN LAYANG - Yaumil Fauzi; Hera Widyastuti (Institut Teknologi Sepuluh Nopember (ITS), 2017)
The increase of vehicles is one of the impacts of activity growth in a region. The high number of vehicles has animpact on the high saturation rate and the decreasing level of effectiveness and performance through Gajah Mada MedanStreet. One of the solutions offered for performance improvement in Gajah Mada Street is the construction of flyover.Therefore, it is necessary to analyze the performance alteration due to the constructed of flyover.The analysis processdevelopment in Gajah Mada Street is conducted on the number of vehicles, speed, capacity, and delay analysis at theintersection. From the analysis result obtained the volume roads, degree of saturation, travel time and forecasting from GajahMada Street.